Microgranular variant of acute promyelocytic leukemia with der(17) ins(17;15): A case report and review of the literature - GUAN, HONGZAI (Exp Ther Med, 2015)
Acute promyelocytic leukemia (APL) with variant translocations is rare. The patient of the present case report, a 2-year-old male with a microgranular variant of APL carrying der(17) ins(17;15) translocation, exhibited fever and epistaxis. The complete blood count showed marked leukocytosis with 72% atypical promyelocytes, anemia and thrombocytopenia. Conventional cytogenetic analysis of the bone marrow cells revealed a karyotype of 47, XY, add(3)(q29), −7, ins(17;15)(q12;q14q22),+21,+mar. The promyelocytic leukemia/retinoic acid receptor α (PML/RARα) rearrangement and insertion were confirmed by fluorescence in situ hybridization. The PML/RARα transcripts were not detected by the reverse transcription polymerase chain reaction, and the patient was diagnosed with microgranular variant M3 APL. The patient achieved remission after a 30-day treatment and was still in remission during a recent follow-up. The present findings suggest that the ins(17;15) variant in APL may not be associated with an unfavorable prognosis. In summary, we reported an extremely rare case of APL with der(17) ins(17;15) abnormality in a pediatric patient and reviewed the literature.